Konsep Pendidikan dalam Perspektif Hadits Nabi Muhammad SAW - Amrona, Yassir Lana; Nurhuda, Abid; Assajad, Anas; Al Fajri, Muhammad; Bin Engku Ab Rahman, Engku Shahrulerizal (Fahima, 2024)
Education has a very integral position in life so implementing it requires cooperation from all parties. Educators are no exception, they play a very important role and have a strategic place in it. So an ideal example is needed, namely the Prophet Muhammad, regarding what the educational concept model should be. This research aims to describe the concept of educators from the perspective of the Prophet’s Hadith. The method used is qualitative with a library study approach technique, while data collection uses a documentation model from primary and secondary sources. After the data is collected, the content is analyzed and concluded. The research results show that an educator is someone who is a role model and helps his students develop their full potential, character, morality, and integrity so that they can be competent Personal- Religiously, Social- Religiously, and Professional- Religiously